ANALISIS KUALITAS AIR BERSIH DI PERUMAHAN SEKITAR RUMAH POTONG HEWAN (RPH) PEKANBARU UNTUK RANCANGAN HANDOUT MATERI PENCEMARAN LINGKUNGAN KELAS X SMA - Dwi Tira Nengsih; Darmawati Darmawati; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research is to find out how the water quality of the wellbore around Pekanbaru Abattoir and produce a handout design of high school environmental X class pollution material. The study was conducted at the Microbiology Laboratory of the Faculty of Medicine, University of Riau, the Chemical Laboratory of the Faculty of Fisheries and Marine Sciences, the research sample was taken at the wellbore of a resident's house around RPH Pekanbaru. The research took place in July-November 2019. The study consisted of two stages, namely the analysis of clean water quality and the handout design stage. The stage of field data collection was carried out with descriptive research, data collection by survey methods, determination of sampling points by purposive sampling. The parameters in the study were total coliform, Eschericia coli, pH, Nitrite (NO2), Nitrate (NO2), turbidity, color, odor and perception of the community around RPH. The results showed that overall clean water quality was not good and did not meet clean water quality requirements where the parameters of total coliform, Escherichia coli, pH, Nitrite (NO2), turbidity, color, and odor obtained results that exceeded the standard quality and Nitrate parameters ( NO3) is in accordance with the quality standards required by Minister of Health Regulation No. 32 of 2017. Based on an analysis of the potential results of the study, a handout of environmental pollution material for the learning of Biology in class X has been designed.Key Words: Animal Slaughter house, Clean water quality, Handout.